Healthier harvests: How Odisha is leading the way by mainstreaming nutritious rice - Tiwari, Ankita (International Rice Research Institute, 2025)
India faces a dual burden of malnutrition and lifestyle diseases, with high rates of stunting, wasting, anaemia, and diabetes. In Odisha, where rice is consumed daily by most rural households, nutrition-sensitive interventions through rice offer a practical solution. The Specialty Rice Project, a collaboration between the Government of Odisha, IRRI, and ICAR, promotes adoption of nutritionally enhanced rice varieties rich in zinc and protein and with low glycemic index. Targeting 5,000 lead farmers across four districts, the project integrates varietal demonstrations, mini-kit trials, women-led Nutri-cafeterias, local seed production, and consumer awareness campaigns. In Bolangir district, farmers and women’s groups produced four tons of seed and ten tons of grain, creating premium market opportunities and fostering community-driven dissemination. Household trials confirmed cultural acceptance, while farmer training strengthened capacity across the seed value chain. This approach demonstrates that embedding nutrition in staple crops can improve health outcomes, support livelihoods, and offer a scalable model for nutrition-sensitive agriculture.